The effect of activity ratios, liquidity, and profitability on the dividend payout ratio - Arsyad, Muhammad; Haeruddin, Sitti Hartati; Muslim, Muslim; Pelu, Muhammad Faisal A. R. (Universitas Sam Ratulangi, 2021)
Dividends are a significant factor in investors' investment interests, so that dividend policy is a critical factor for companies to retain their shareholders. On this purposes, the companies must improve financial performance, especially activity ratios, liquidity ratios, and profitability ratios in this condition. The consumer goods industry sector is one of the industries that play a significant role in the capital market as they have rapid business competition. Until May 2020, the performance condition of companies in the consumer goods industry was experiencing less than optimal conditions as the manufacturing sector weakened at 22.0% due to the weakening of Indonesia's manufacturing Purchasing Managers' Index (PMI). The condition indicates that the impact of a decrease in the company's liquidity performance is a decrease in demand for manufactured goods which gives results in a decrease in profitability performance, and a less than optimal turnover of company assets in the consumer goods industry sector. This study uses manufacturing companies in the consumer goods industry listed on the Indonesia Stock Exchange from 2015 to 2019 as a sample. Multiple regression analysis results show that return on investment has a positive and significant effect on the dividend payout ratio. This result implies that the profitability ratio is a positive signal for investors in the capital market regarding the company's dividend policy.